Constructions of self: ethical overtones in surprising locations. Issue 2 (5th December 2005) - Kinsella, E A
Abstract : Little discussion has occurred in the health profession literature with respect to how the "self" is constructed, despite the imagination and attention it has garnered from philosophers and theorists in various other disciplines. Yet this subject has surprisingly ethical overtones for health professional education and practice. In this paper notions of the self are briefly considered and it is suggested that a narrative and dialogic view of self can contribute to insights about ethical practice in the health professions. Subtle issues with respect to how relationship and language may be used to wield power are revealed and discussed; and awareness about how such power is used in practice is highlighted as a crucial issue. The assumptions practitioners make with respect to constructions of self are ethically important and this topic warrants consideration in the medical humanities.